Overview of the incompressible Navier–Stokes simulation capabilities in the MOOSE framework. (May 2018) - Peterson, John W.; Lindsay, Alexander D.; Kong, Fande
Highlights: We present an open source FEM for the incompressible Navier-Stokes equations based on the MOOSE framework. Coordinate system agnostic weak formulation. SUPG/PSPG stabilized finite element formulation. Discussion of object-oriented software design. Sample code and input file snippets. Lid-driven cavity, axisymmetric diffuser, 3D sphere flow calculations. Abstract: The Multiphysics Object Oriented Simulation Environment (MOOSE) framework is a high-performance, open source, C++ finite element toolkit developed at Idaho National Laboratory. MOOSE was created with the aim of assisting domain scientists and engineers in creating customizable, high-quality tools for multiphysics simulations. While the core MOOSE framework itself does not contain code for simulating any particular physical application, it is distributed with a number of physics "modules" which are tailored to solving e.g. heat conduction, phase field, and solid/fluid mechanics problems. In this report, we describe the basic equations, finite element formulations, software implementation, and regression/verification tests currently available in MOOSE'snavier_stokes module for solving the Incompressible Navier-Stokes (INS) equations.